RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS DETERMINATION OF MEBENDAZOLE AND THE TWO PRESERVATIVES METHYLPARABEN AND PROPYLPARABEN IN PHARMACEUTICAL ORAL SUSPENSION DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A rapid, accurate, specific, linear, and sensitive reverse phase-HPLC method has been developed and validated for the simultaneous determination of Mebendazole (MEB), Methylparaben (MP) and Propylparaben (PP) in pharmaceutical oral suspension dosage form. The chromatographic separation was performed on (Inertsil ODS-3V) C18 Column (250mm × 4.6mm, 5μm particle size) using a mobile phase: Methanol, 0.05M monobasic potassium phosphate, Acetonitrile (48:32:20v/v), at a flow rate of 1.5 ml/min and 30°C column temperature with the detection wavelength at 247nm. The retention times of MP, MEB and PP were 2.83 min, 4.14 min and 4.75 min respectively. The linearity was performed in the concentration range of 3.6-5.4μg/ml (MP), 40-60μg/ml (MEB), and 0.4-0.6μg/ml (PP) with a squared correlation coefficient of 0.999, 0.999 and 0.9994 for MP, MEB and PP respectively. The percentage purity of MP, MEB and PP was found to be >99.0%. The Proposed method has been validated for specificity, linearity, precision, accuracy, ruggedness and robustness which were within the acceptance limit according to ICH guidelines and the developed method was successfully employed for routine quality control analysis in the combined pharmaceutical dosage forms.